Renal supportive care programs: An observational study assessing impact on hospitalization and survival outcomes. Issue 6 (9th March 2021) - Chia, Xiu Xian; Johnston, Rebecca; Aggarwal, Rajesh; Huynh, Thang; Notaras, Stephanie; Zekanovic, Dragana; Gordon, Katrina; Sasongko, Victoria; Makris, Angela
Abstract: Aim: Renal supportive care (RSC) programs are used to manage non‐dialysis end‐stage kidney disease (ESKD) patients. The aim of this study was to analyse the impact of RSC programs on hospitalization and survival outcomes in these patients. Methods: A retrospective, single‐centre observational cohort study of non‐dialysis ESKD patients was undertaken. Hospitalizations and survival from eGFR≤15 ml/min was compared between patients managed in an RSC program (RSC group) and patients receiving standard conservative therapy (non‐RSC group). Local databases, physician letters and electronic medical records were used for data collection. Prevalent patients from 2013 to 2017 with eGFR ≤15 ml/min were included. Cox proportion hazard testing and generalized linear modelling was undertaken to adjust for confounders. Results: A total of 172 patients were included (95 RSC; 75 non‐RSC). The median age was 82 years [IQR 78–85], 46% were male, the median Charlson‐comorbidity Index was 5 [IQR 4–7]. The RSC group had significantly lowered haemoglobin level (102 g/L vs. 111 g/L) and fewer English‐speakers (34% vs. 44%). RSC was associated with the decreased number of days in hospital per year (estimated means 46.6 days [95% CI 21–67] vs. 83.2 days [95%CI 60.5–105.8]; p = .01) and decreased number of hospital admissions per year (estimated means 5.4 [95%CI 2.1–8.8] vs. 12.3 [95%CI 8.2–16.4]; p = .01) compared with non‐RSC. Median overall survival from eGFR≤15 in the entire cohort was 735 days, with no significant difference between RSC and non‐RSC groups ( p = .9), both unadjusted and adjusted for confounders. Conclusion: RSC programs can significantly decrease the number and length of hospitalizations in conservatively managed ESKD patients. SUMMARY AT A GLANCE: The study analysed the impact of renal supportive care (RSC) on hospitalization and survival outcomes of non‐dialysis ESKD patients. RSC can significantly decrease the number and length of hospitalisations in conservatively managed ESKD patients.